2008
DOI: 10.1111/j.1526-4610.2008.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Almotriptan in Adolescents: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Oral almotriptan was efficacious for relieving migraine headache pain in adolescents, with the 12.5-mg dose associated with the most favorable efficacy profile with respect to relieving headache pain and associated symptoms of migraine (photophobia and phonophobia). Almotriptan treatment was well tolerated in this adolescent population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 28 publications
0
54
1
1
Order By: Relevance
“…8 Almotriptan is approved by the Food and Drug Administration for acute migraine therapy in adolescents. 40 Several other triptans have been studied in adolescents and children and used off-label, most notably nasal spray sumatriptan. 8 In case reports, IV verapamil seems effective for acute hemiplegic migraine.…”
mentioning
confidence: 99%
“…8 Almotriptan is approved by the Food and Drug Administration for acute migraine therapy in adolescents. 40 Several other triptans have been studied in adolescents and children and used off-label, most notably nasal spray sumatriptan. 8 In case reports, IV verapamil seems effective for acute hemiplegic migraine.…”
mentioning
confidence: 99%
“…Numerous triptans have been studied in adolescent migraine, most with positive results. Triptans most recently studied include almotriptan [ 23 ] and zolmitriptan nasal spray [ 24 ] and tablet [ 25 ]. Others have been studied; however, the short duration of headache in adolescents, high placebo response rate, and few randomized controlled trials have resulted in limited compelling data and no formal approval for use in those younger than 18 years.…”
Section: Abortive Treatmentmentioning
confidence: 97%
“…This was based on a randomized, doubleblind, placebo controlled trial of almotriptan in 866 adolescents (age 12-17), which found a 2-h pain-relief rate that was significantly higher for all doses of almotriptan -6.25 mg (71.8%), 12.5 mg (72.9%) and 25 mg (66.7%) compared with placebo (55.3%) [54].…”
Section: Acute Treatmentmentioning
confidence: 99%